Kloning gen LEAFY kakao dari jaringan bantalan bunga aktif Cloning of cacao LEAFY gene from the active flower cushions - Tetty CHAIDAMSARI; Rita HAYATI; Auzar SYARIEF; Aswaldi ANWAR; Djoko SANTOSO (Menara Perkebunan, 2009)
SummaryAttempts to improve productivity of cacaoplantations lead us to study the molecularmechanism of flowering. In the model speciesArabidopsis thaliana as well as some otherspecies, LEAFY is a central regulatory gene forthe transition of shoot apical meristems toflowering meristems. Different from that ofArabidopsis, cacao inflorescence is acauliflorous type, by which flowers can developrepeatedly from the same flower cushion on thetrunk. In this research, a LEAFY homolog wasisolated from active flower cushion with RT-PCRusing a pair of DNA primer specifically designedto isolate its complete cds. Gel electrophoresisexamination indicated the presence of a 1.2 kbamplicon. Purified from the gel, this DNAfragment was cloned into competent cells ofE. coli XL1 Blue using pGEM-T Easy cloningvector at an orientation according to the T7promoter of the plasmid. Sequence analysis usingBLASTX, showed that the amplicon was LEAFY(LFY) homolog. Alignment analysis using ClustalW indicated that the cTcLFY highly homologousto those from other perennial crops such ascitrus, grape, apple and poplar. The highesthomology (conserved region) was found in the Cterminal of the encoded proteins.RingkasanUsaha untuk meningkatkan produktivitasperkebunan kakao telah mendorong penelitianmolekuler tentang mekanisme pembungaankakao. Pada tanaman model Arabidopsis thalianadan lainnya, LEAFY merupakan gen kunci dalamtransisi meristem tunas jadi meristem bunga.Berbeda dengan sistem pada Arabidopsis,pembungaan kakao termasuk tipe cauliflorous,bunga dapat muncul dari bantalan bunga yangsama sepanjang tahun. Dalam penelitian inihomolog LFY diisolasi dari bantalan bunga aktifmenggunakan RT-PCR dengan sepasang primerspesifik yang dirancang berdasarkan sekuenDNA di kedua ujung gen tersebut. Pemeriksaangel elektroforesis menunjukkan adanya amplikontunggal berukuran 1,2 kb. Setelah dimurnikandari gel, amplikon dapat diklon ke dalam selkompeten E. coli galur XL1 Blue menggunakanvektor pGEM-T Easy dengan orientasi yangsesuai dengan promoter T7 dari vektor. AnalisisBLASTX sekuen DNA membuktikan bahwaamplikon tersebut adalah homolog dari genLEAFY. Analisis penjajaran dengan mengguna-kan ClustalW menunjukkan bahwa gen cTcLFYtersebut memiliki homologi yang tinggi dengangen sejenis dari tanaman keras lainnya sepertitanaman jeruk, anggur, apel dan poplar.Homologi tertinggi (daerah terkonservasi)terdapat pada ujung (terminal) C dari proteinyang disandinya.